1997
DOI: 10.1111/j.1525-1314.1997.00059.x
|View full text |Cite
|
Sign up to set email alerts
|

Partial melting during tectonic exhumation of a granulite terrane: an example from the Larsemann Hills, East Antarctica

Abstract: A B S TR A CT Anatectic migmatites in medium-to low-pressure granulite facies metasediments exposed in the Larsemann Hills, East Antarctica, contain leucosomes with abundant quartz and plagioclase and minor interstitial K-feldspar, and assemblages of garnet-cordierite-spinel-ilmenite-sillimanite. Qualitative modelling in the system K 2, in conjunction with various P-T calculations indicate that the high-grade retrograde evolution of the terrane was dominated by decompression from peak conditions of c. 7 kbar a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
66
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(78 citation statements)
references
References 64 publications
11
66
1
Order By: Relevance
“…Despite of the absence of direct evidence for ocean closure, the compressional and extensional deformation patterns and clear decompressional textures are preserved in metamorphic rocks from Prydz Bay Carson et al, 1995Carson et al, , 1997Fitzsimons, 1996). This is compatible with a collisional orogeny followed by extensional collapse of a thickened crust.…”
Section: Nature and Role Of The Prydz Beltmentioning
confidence: 86%
See 1 more Smart Citation
“…Despite of the absence of direct evidence for ocean closure, the compressional and extensional deformation patterns and clear decompressional textures are preserved in metamorphic rocks from Prydz Bay Carson et al, 1995Carson et al, , 1997Fitzsimons, 1996). This is compatible with a collisional orogeny followed by extensional collapse of a thickened crust.…”
Section: Nature and Role Of The Prydz Beltmentioning
confidence: 86%
“…The high-grade metamorphic rocks exposed along the Prydz Bay coastline comprise two lithological associations, mafic-felsic composite orthogneisses and migmatitic paragneisses (Fitzsimons and Harley, 1991;Dirks and Wilson, 1995). The peak metamorphic conditions were estimated at 5.5-7.0 kbar and 800-860 • C (Stüwe and Powell, 1989;Thost et al, 1994;Fitzsimons, 1996;Carson et al, 1997). Geochronological studies suggest that the high-grade metamorphism, compressional and subsequent extensional deformations, and the emplacement of syn-to post-tectonic granites all took place in a short time span of 550-490 Ma (Zhao et al, 1992(Zhao et al, , 1995bHensen and Zhou, 1995;Carson et al, 1996;Fitzsimons et al, 1997).…”
Section: Geological Settingmentioning
confidence: 99%
“…However, an increasing number of studies describe felsic pegmatites that are considered to be derived by direct partial melting rather than by fractional crystallisation of a parent granite. Examples include the Münchberg Massif, Germany (Franz and Smelik, 1995); Brattstrand Bluffs, East Antarctica (Fitzsimons, 1996); Larsemann Hills, East Antarctica (Carson et al, 1997); Urdach and Espéchère, in the western Pyrénées (Pin et al, 2006); the Fraser Lake area of Northern Saskatchewan, Canada (McKechnie et al, 2012); and the Moldanubian domain of the Bohemian Massif, Czech Republic (Melleton et al, 2012). In many cases granitic pegmatites are described as being derived by extended fractional crystallisation of a fertile parent granite, even where a parent granite body remains enigmatic (Crouse and Č erný , 1972;Jahns and Ewing, 1976;Stilling et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The paragneisses on Stornes Peninsula, Stornesbukta and Seal Cove of Mirror Peninsula contain borosilicate minerals prismatine and grandidierite (Carson et al, 1995b;Cooper et al, 2009;Grew et al, 2006Grew et al, , 2007Ren and Liu, 1994;Ren and Zhao, 2004), and a sapphirine-bearing assemblage was also reported from Stornes Peninsula (Grew et al, 2006Ren et al, 2008;Tong and Liu, 1997). The paragneisses experienced extensive partial melting and migmatization (Dirks et al, 1993), and were considered to represent part of an extensive basinal sedimentary sequence extending about 130 km from the southern Rauer Group to the Bolingen Islands (Carson et al, 1995a(Carson et al, , 1997. The mafic-felsic orthogneisses and paragneisses were generally interpreted as tectonically interleaved Proterozoic basement and sedimentary cover sequence in the region (Carson et al, 1995a;Dirks and Hand, 1995;Dirks et al, 1993;Fitzsimons and Harley, 1991;Sheraton et al, 1984;Stüwe et al, 1989).…”
Section: Geological Backgroundmentioning
confidence: 99%
“…This controversy resulted from the contrasting interpretations of the metamorphic P-T history of the Larsemann Hills and adjacent areas. For instance, it was thought that decompression-dominated P-T paths in the regions evolved during a single Pan-African (~530 Ma) metamorphic event (Carson et al, 1997;Fitzsimons, 1996Fitzsimons, , 1997Grew et al, 2006;Thost et al, 1994), but other studies suggested that the paragneisses experienced both the~1000 Ma and the~530 Ma high-grade metamorphic events (Dirks and Hand, 1995;Tong and Liu, 1997;Tong et al, 1998Tong et al, , 2002Zhang et al, 1996). Latter suggestion is further supported by recent new SHRIMP U-Pb age data from the paragneisses in the region (Grew et al, 2012;Wang et al, 2008).…”
Section: Introductionmentioning
confidence: 99%